Model of Internalization of Religious Values in the Formation of Civil Rights Legal Awareness Based on Collaborative Governance - Oktio Frenki Biantoro; Fahmy Asyhari (CV. Edujavare Publishing, 2026)
Civil Servants (ASN) are a key element of government administration and are required not only to be professional but also to possess a strong legal awareness and public service ethics. This study aims to analyze the relationship between religious values, legal awareness, and Collaborative Governance in the governance of the Salatiga City DPRD Secretariat. The study used a qualitative approach with a descriptive case study design, while data were collected through interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results of the study indicate that religious values internalized through Khotmil Qur'an activities, social awareness, and religious tolerance serve as the foundation of organizational ethics that strengthen the character of ASN, while legal awareness is built through legal training, work discipline, and the use of information technology to support institutional transparency and accountability. In addition, Collaborative Governance serves as a governance framework that connects moral values and legal compliance with communication, trust, and shared responsibility in public services. Thus, the governance of the Salatiga City DPRD Secretariat demonstrates that the integration of religious values, legal awareness, and a collaborative work culture can form a bureaucracy that is ethical, professional, humanistic, and responsive to the needs of the community.